The m6A Reader YTHDF1 Accelerates the Osteogenesis of Bone Marrow Mesenchymal Stem Cells Partly via Activation of the Autophagy Signaling Pathway - Xiang Gao; Jian Wang; Yibo Wang; Weixu Li; Zhijun Pan (Hindawi Limited, 2023)
N6-methyladenosine (m6A) mRNA methylation has emerged as an important player in many biological processes by regulating gene expression. As a crucial reader, YTHDF1 usually improves the translation efficiency of its target mRNAs. However, its roles in bone marrow mesenchymal stem cells (BMSCs) osteogenesis remain largely unknown. Here, we reported that YTHDF1, an m6A reader, is highly expressed during osteogenic differentiation of BMSCs. Upregulation of YTHDF1 increased osteogenic differentiation and proliferation capacity of BMSCs. Accordingly, downregulation of YTHDF1 inhibited osteogenic differentiation and proliferation capacity. Possible underlying mechanisms were explored, and analysis revealed that YTHDF1 could affect autophagy levels, thus regulating osteogenesis of BMSCs. In an in vivo study, we found that upregulation of YTHDF1 accelerates fracture healing with elevated bone volume fraction and trabecular thickness. Taken together, our study revealed that m6A reader YTHDF1 accelerates osteogenic differentiation of BMSCs partly via the autophagy signaling pathway. These findings reveal a previously unrecognized mechanism involved in the regulation of BMSCs osteogenesis, providing new ideas and target sites for the treatment of fracture.